PENGARUH KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN: STUDI KASUS PERUSAHAAN CONSUMER NON-CYCLICALS - Priyatma, Tunggul; Afandi, Yusron (POLITEKNIK LP3I JAKARTA, 2023)
This study aims to determine and analyze the effect of environmental performance on company value with environmental accounting disclosure as a moderation variable. This research method uses quantitative methods. The data in this study is secondary data, which is in the form of annual financial reports and sustainability reports of consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) for 2018 – 2022. The population in this study amounted to 59 companies and with a total research sample of 80 observation data. The sampling technique used in this study is the purposive sampling method. Data analysis was performed by panel data regression analysis and moderated regression analysis. The results of this study indicate that environmental performance does not have a significant effect on firm value, environmental accounting disclosure can moderate or improve the relationship effect of environmental performance on company value. This study has several limitations, namely that the independent variable only consists of one kind, the sample in the study is only from consumer non-cyclicals sector companies with a research period of 2018 - 2022. So, suggestions for future research can add research variables and use other company sectors. Keywords: Environmental Performance, Environmental Accounting Disclosures, Firm Value, Stock Price, Stakeholders.